Pengaruh Kompetensi, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan CV Geopasi Trisuci - Oktavyani, Bunga Annisa; Gumilar, Dedi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The approaches used in quantitative research are verification and descriptive. This research was conducted at CV Geopasi Trisuci with a sample of 35 employees. The results of the study indicate that (1) the competency variable has a partial negative effect on employee performance; (2) the work motivation and work discipline variables have a positive effect on employee performance; (3) the competency, work motivation, and work discipline variables have a partial effect on employee performance; and (4) the competency, motivation, and work discipline variables have an effect on employee performance of 65.6%, while other variables not included in this study are 34.4%